The Impact of Destination Brand Authenticity on Tourist Loyalty in Yogyakarta: A Study on Generation Z - Rayhan Razaqi Sjuhada; Naila Zulfa (Pelopor Publikasi Akademika, 2024)
This research aims to determine the effect of authenticity on loyalty through the interaction of tourists in Yogyakarta. The City of Yogyakarta, a tourist destination located in the heart of the island of Java, is designated as a Super Priority Tourism Destination area to accelerate the regional economy. Until July 2022, 3.9 million recorded tourists were visiting Yogyakarta City destinations. Understanding tourist loyalty can help destination marketers reduce marketing costs. In previous studies, it has been found that tourist loyalty is influenced by destination brand authenticity and is supported by the involvement of destination brand engagement. This research is quantitative and was carried out using a survey method. Data analysis was performed using simple and multiple regression analysis using the SPSS (Statistical Package for Service Solutions) version 26. The results showed a direct influence of brand authenticity and engagement on tourist loyalty and an indirect effect. Between brand authenticity and tourist loyalty through destination brand engagement. Tourist destination managers, especially D.I Yogyakarta, can use the results of this research to design the Yogyakarta City destination brand in a marketing strategy that can re-attract tourists in Yogyakarta.